Cellular target identification of Withangulatin A using fluorescent analogues and subsequent chemical proteomics. Issue 57 (26th June 2019) - Zhu, Tianyu; Chen, Chen; Wang, Sisi; Zhang, Yi; Zhu, Dongrong; Li, Lingnan; Luo, Jianguang; Kong, Lingyi
Abstract : Find the target of Withangulatin A with the combination of fluorescent probes and chemical proteomics. Abstract : Withangulatin A (WA) has been reported to exhibit potent antitumor activity. However, its possible mechanism and direct proteomic targets remain unknown. Herein we report the subcellular localization of WA by designing and synthesizing its fluorescent analogues with coumarin moieties. Furthermore, sarco/endoplasmic reticulum calcium-ATPase (SERCA)2 was identified as the potential target of WA for its antitumor activity by chemical proteomics.